Solitary cystic tuberculosis of the distal femur and proximal tibia in children - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
Pediatric skeletal (extraspinal) tuberculosis may mimic pyogenic infections and bone tumors. The aim of this study was to show a multimodality approach to the correct diagnosis and to evaluate the long-term clinical and radiological results of curettage and antituberculosis treatment. Between 2004 and 2012, we treated eight children (five boys, three girls) with histologically proven solitary cystic tuberculosis of the proximal tibia and distal femur. The average age at presentation was 4 years (range, 2-6 years). Except for one case with metadiaphyseal involvement, all lesions were located in the metaphysis and crossed the physis in three. The patients were managed by curettage without bone grafting, followed by antituberculosis therapy. The average follow-up was 4 years (range, 2-7 years). All children achieved complete clinical and radiological healing without any residual lesion or recurrence. In three cases with epiphyseal involvement, the growth plate maintained its function and gradually remodeled within 24 months, without any deformity. No surgical complication was observed. The diagnosis of pediatric skeletal tuberculosis can be made with a good correlation of clinical, radiological, and histological findings. High healing rates can be achieved with surgical debridement and chemotherapy.
Keywords: antituberculosis chemotherapy; children; curettage; skeletal tuberculosis; SKELETAL TUBERCULOSIS; OSTEOMYELITIS; BONE